Assistance to Village-Owned Enterprise Treasurers in Preparing BUMD Village Financial Reports in Pandan Lagan Village - Ningsih, Ovtafia Yulia; Nurjali, Nurjali; Wandi, Wandi (Media for Empowerment, Mobilization, and Innovation in Research & Community, 2025)
This community service program aims to enhance the capability of the treasurer of the Village-Owned Enterprise (BUMDesa) Pandan Lagan in preparing financial statements in accordance with basic accounting principles and applicable regulations. BUMDesa serves as a key pillar of rural economic development that requires transparent and accountable financial governance. The program was carried out through training and direct mentoring using workshop-based approaches, practical exercises in financial report preparation, and evaluation of participants’ outcomes. The results indicate an increase in the treasurer’s understanding and skills in preparing BUMDesa financial reports, including cash flow statements, simple balance sheets, and profit-and-loss statements for each business unit. This mentoring program has a positive impact on financial transparency and community trust in BUMDesa financial management.